The Akhenaten Colossi of Karnak - Manniche, Lise (American University in Cairo Press, 2010)
The author presents the history of the discovery of the statue fragments from 1925 to the present day; the profusion of opinions on the appearance of the king and his alleged medical conditions; and the various suggestions for an interpretation of the perplexing evidence. A complete catalogue of all major fragments is included, as well as many pictures not previously published.